Review on Ruminant Nutrition Research - Haryanto, Budi (Indonesian Animal Sciences Society, 2012)
Research works in ruminant nutrition have been widely published, especially those related to the energy and proteinutilization. The energy and protein requirements for maintenance and production in tropical regions may be different from thosein the subtropical areas. Responses of different species of ruminants to energy and protein supplements were also observed. Thesynchronization of energy and protein availability has been considered as an important strategy in affecting the microbialfermentative process in the rumen and in affecting the animal performance. The inclusion of long-chained unsaturated fatty acidsin the diets has been successfully affecting milk production with higher concentration of unsaturated fatty acids. Feedstuffscharacteristics in terms of their degradability and fermentation by rumen microbial enzymes have been intensively studied;however, further experimentations are still needed to elucidate the specific fate of its nutritive components in the rumen andtissue levels.Key words: Ruminants, energy, protein, nutrition